Early Adult Happiness During the Quarter-Life Crisis Period in Terms of Self-Esteem - Qonitah, Rizky; Ramadhani, Ayunda; Rahayu, Diah; Rahman, Nadya Novia (Psyche 165 Journal, 2025)
Early adults undergoing their developmental tasks have the potential to experience a quarter-life crisis as a life challenge that brings about several negative impacts. These problems can be overcome if early adults have happiness in their lives. Happiness can be increased by instilling self-esteem obtained from within themselves and those around them. This study aims to determine the relationship between self-esteem and happiness in early adults experiencing a quarter-life crisis . This study uses a quantitative approach method. The sample of this study was 209 early adults experiencing a quarter-life crisis determined through a purposive sampling technique . The measuring instrument used in this study was a Likert -type scale , namely the happiness scale and the self-esteem scale. The happiness scale consists of 14 valid items with a reliability value of 0.712 and the self-esteem scale consists of 27 valid items worth 0.848 obtained through a reliability test using Cronbach's Alpha so that both scales can be declared reliable . The happiness scale and the self-esteem scale are declared normal with p-values of 0.065 and 0.200, respectively. The data analysis technique for this study uses the Pearson product moment correlation test . The results of this study indicate that there is a significant positive relationship between self-esteem and happiness in early adults experiencing a quarter-life crisis with a calculated r value of 0.0574 > r table 0.114 and a sig value of 0.000 (p < 0.05).